Pertalian Angka dan Makna dalam Al-Qur’an Mempertemukan Relasi Antarayat dalam Kajian al-I‘jaz al-‘Adadi dan Kajian Tafsir al-Qur’an bi al-Qur’an - Izza Rohman (Qur'an and Hadith Academic Society, 2014)
This paper looks into intra-Qur’anic connections derived from serious efforts either to reveal what-so-called the mathematic miracle of the Qur’an or to interprete the Qur’an with the Qur’an. In doing so, it seeks to explore the compatibility of the two as well as the possibility to make both approaches to the Qur’an mutually inclusive. In this regard, this article deals particularly with some examples of connection among Qur’anic verses pursued through various attempts to find the alleged numerical code in the Qur’an, and compares them to what selected tafsirs have disclosed.